Role of the major homology region of human immunodeficiency virus type 1 in virion morphogenesis. - Mammano, F (1994)
Retroviral capsid (CA) proteins contain a uniquely conserved stretch of 20 amino acids which has been named the major homology region (MHR). To examine the role of this region in human immunodeficiency virus type 1 morphogenesis and replication, four highly conserved positions in the MHR were individually altered by site-directed mutagenesis. Conservative substitution of two invariant residues (glutamine 155 and glutamic acid 159) abolished viral replication and significantly reduced the particle-forming ability of the mutant gag gene products. Conservative substitution of the third invariant residue in the MHR (arginine 167) or of an invariably aromatic residue (tyrosine 164) had only a moderate effect. However, removal of the extended side chains of these amino acids by substitution with alanine prevented viral replication and affected virion morphogenesis. The replacement of tyrosine 164 with alanine substantially impaired viral particle production. By contrast, the substitution of arginine 167 with alanine had only a two- to threefold effect on particle yield but led to the formation of aberrant core structures. The MHR mutant which were severely defective for particle production had a dominant negative effect on particle formation by the wild-type Gag product. The role of the MHR in the incorporation of the Gag-Pol precursor was examined by expressing the Gag and Gag-Pol polyproteins individually from separate plasmids. Only when the two precursor polyproteins were coexpressed did processed Gag and Pol products appear in the external medium. The appearance of these products was unaffected or only moderately affected by substitutions in the MHR of the Gag-Pol precursor, suggesting that the mutant Gag-Pol precursors were efficiently incorporated into viral particles. The results of this study indicate that specific residues within the MHR are required both for human immunodeficiency virus type 1 particle assembly and for the correct assembly of the viral core. However, mutant Gag and Gag-Pol polyproteins with substitutions in the MHR retained the ability to interact with wild-type Gag protein.